2018
DOI: 10.1055/s-0044-101756
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Thyroid and Blood Pressure in Euthyroid Adults: A 9-Year Longitudinal Study

Abstract: Longitudinal studies considering associations between thyroid function in the reference range (RR) with blood pressure (BP) are scarce and contradictory. We aimed to investigate the associations of serum thyrotropin (TSH) and free T4 (FT4) with different components of BP also incident prehyperetension (preHTN) and HTN during a 9-year follow-up. A sum of 2282 euthyroid individuals from an ongoing population-based cohort study were selected. A sex-stratified multivariate generalized estimating equation (GEE) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…Findings from above studies suggest a U‐shape relationship between THs within the whole range (subclinical and overt hyperthyroidism, euthyroidism, and subclinical and overt hypothyroidism) and BP levels. However, to the best of our knowledge, few studies have analyzed the relationships between THs, TSH levels and elevated BP in euthyroid subjects . In the present study, we found positive linear relationships between FT3, FT4 concentrations within the reference range and elevated BP.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Findings from above studies suggest a U‐shape relationship between THs within the whole range (subclinical and overt hyperthyroidism, euthyroidism, and subclinical and overt hypothyroidism) and BP levels. However, to the best of our knowledge, few studies have analyzed the relationships between THs, TSH levels and elevated BP in euthyroid subjects . In the present study, we found positive linear relationships between FT3, FT4 concentrations within the reference range and elevated BP.…”
Section: Discussionsupporting
confidence: 66%
“…Few studies have explored the relationships of FT3, FT4, TSH levels with the prevalence ofelevated BP. To the best of our knowledge, only a small‐scale cohort study (n = 2282) investigated whether FT4 and TSH within reference range were risk factors for elevated BP in Tehran population . Their findings indicated that a 1 ng/dL higher FT4 was related to 40% increased risk of elevated BP (OR [95%CI]: 1.40 [1.02‐1.90]), but no significant relationship was observed between TSH and elevated BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, the meta‐analysis of He et al showed the relationship of TSH with increased clinic systolic and diastolic blood pressures, but it could not explain the high heterogeneity in the results of analysis ( I 2 = 90%) . In addition, many recent clinical studies did not support the results . Moreover, the effect of the two thyroid function indicators free triiodothyronine (FT3) and free thyroxine (FT4), which had a direct action, on the blood pressure was still not known .…”
Section: Introductionmentioning
confidence: 99%